Metropolisation and the Evoluti on of Systems of Cities in the Czech Republic, Hungary and Poland Since 1950 - Natalia Zdanowska (DETUROPE)
This article examines the evolution of systems of cities in the Czech Republic, Hungary and Poland since 1950, and especially since the fall of the Berlin Wall in 1989 when Central and Eastern European cities started to experience the process of metropolisation. This period corresponds to an intense globalisation of the economy which has been characterised by some researchers as an emergence of a world urban system. While the metropolises of formerly industrialised countries had already been strongly interconnected on a macro-regional level, Central and Eastern European countries took on the unique approach of prioritising relations directly at an international level. In addition to its highly exacerbated characteristics, the metropolisation in Central and Eastern Europe has been taking place within a substantially shorter time period in relation to other countries. This article investigates how these phenomena might have influenced the configuration of today’s urban systems. After presenting the methodology used to reconstruct urban agglomerations since 1950 until now, we examine the evolution of the Czech, Hungarian and Polish systems of cities by using several national databases. By analysing the changes in urban hierarchy and new urban patterns, we can stress that after 1989 the metropolisation has rather contributed to raise the predominance of the capital city in the urban systems than to diminish inequalities between the cities.